Relationship between Temperature and Behavior with Pulmonary TB Incidence in Women in the Banyu Urip Health Center Surabaya, Indonesia - Fenti Nur Aini Amallia1 , Retno Adriyani1 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Tuberculosis was a one of infectious disease caused by Mycobacterium tuberculosis. The transmission of this disease was influenced by environmental factors and poor behaviour. Based on observation result, the working area of Banyu Urip Health Center was a densely populated area. The purpose of this research was to analyze the house physical quality and behaviour with pulmonary TB incidence in women at the working area of Banyu urip health center. This research was observational analytic research with case control study design. The data analysis was using chi square test. The sample was taken by simple random sampling of 30 houses with pulmonary TB patients and 30 house with no pulmonary TB patients. The data collection was using questionnaire, house physical quality measurement was using observation sheets. The result of the study indicate that temperature and behavior have a significant relationship with the existence of Mycobacterium tuberculosis in house air (p<0,05). The conclusion based on chi square test was bedroom temperature and behavior have a relationship with pulmonary TB incidence in women at the working area of Banyu urip health center 2018. The communities were expected to maintain their house physical quality by maintaining the cleanliness of the house and increasing ventilation to facilitate air circulation in the house.